Increased expression of microRNA-15a and microRNA-15b in skeletal muscle from adult offspring of women with diabetes in pregnancy. (8th March 2018) - Houshmand-Oeregaard, Azadeh; Schrölkamp, Maren; Kelstrup, Louise; Hansen, Ninna S; Hjort, Line; Thuesen, Anne Cathrine B; Broholm, Christa; Mathiesen, Elisabeth R; Clausen, Tine D; Vaag, Allan; Damm, Peter
Abstract: Offspring of women with diabetes in pregnancy exhibit skeletal muscle insulin resistance and are at increased risk of developing type 2 diabetes, potentially mediated by epigenetic mechanisms or changes in the expression of small non-coding microRNAs. Members of the miR-15 family can alter the expression or function of important proteins in the insulin signalling pathway, affecting insulin sensitivity and secretion. We hypothesized that exposure to maternal diabetes may cause altered expression of these microRNAs in offspring skeletal muscle, representing a potential underlying mechanism by which exposure to maternal diabetes leads to increased risk of cardiometabolic disease in offspring. We measured microRNA expression in skeletal muscle biopsies of 26- to 35-year-old offspring of women with either gestational diabetes (O-GDM, n  = 82) or type 1 diabetes (O-T1DM, n  = 67) in pregnancy, compared with a control group of offspring from the background population (O-BP, n  = 57) from an observational follow-up study. Expression of both miR-15a and miR-15b was increased in skeletal muscle obtained from O-GDM (both P  < 0.001) and O-T1DM ( P  = 0.024, P  = 0.005, respectively) compared with O-BP. Maternal 2 h post OGTT glucose levels were positively associated with miR-15a expression ( P  = 0.041) in O-GDM after adjustment for confounders and mediators. In all groups collectively, miRNA expression was significantly positively associated with fasting plasma glucose, 2 h plasma glucose and HbA1c. We conclude that fetal exposure to maternal diabetes is associated with increased skeletal muscle expression of miR-15a and miR-15b and that this may contribute to development of metabolic disease in these subjects.